Fluorescence-guided lung nodule identification during minimally invasive lung resections - Tajè, Riccardo; Gallina, Filippo Tommaso; Forcella, Daniele; Vallati, Giulio Eugenio; Cappelli, Federico; Pierconti, Federico; Visca, Paolo; Melis, Enrico; Facciolo, Francesco (Frontiers in Surgery, 2022)
In the last few years, minimally invasive surgery has become the standard routine practice to manage lung nodules. Particularly in the case of robotic thoracic surgery, the identification of the lung nodules that do not surface on the visceral pleura could be challenging. Therefore, together with the evolution of surgical instruments to provide the best option in terms of invasiveness, lung nodule localization techniques should be improved to achieve the best outcomes in terms of safety and sensibility. In this review, we aim to overview all principal techniques used to detect the lung nodules that do not present the visceral pleura retraction. We investigate the accuracy of fluorescence guided thoracic surgery in nodule detection and the differences among the most common tracers used.